Studi Literatur: Implementasi Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Keterampilan Berpikir Kritis IPAS Siswa Sekolah Dasar - Hastuti, Tri Wahyuni; Salimi, Moh. (Universitas Sebelas Maret, 2025)
Along with the development of the era and the demands of the 21st century, student competencies must be developed, especially in 4C skills. This study comprehensively aims to analyze in depth the implementation of the guided inquiry learning model in the context of science learning in Elementary Schools and identify its effectiveness in improving students' critical thinking skills. This study adopts a qualitative approach with the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) framework to ensure transparency and reproducibility of findings. Data collection was carried out through searching various sources, including scientific journal articles, relevant literature, and other publications. The results of this study state that the guided inquiry model has a significant contribution to improving the critical thinking skills of elementary school students in science. This is because it allows students to process and analyze information, thus producing something new to existing concepts. Therefore, the application of the guided inquiry learning model in the context of science learning is an important step in improving the critical thinking skills of elementary school students.Seiring dengan perkembangan zaman dan tuntutan abad ke-21, kompetensi siswa harus dikembangkan khususnya pada keterampilan 4C. Penelitian ini secara komprehensif bertujuan untuk menganalisis secara mendalam implementasi model pembelajaran inkuiri terbimbing dalam konteks pembelajaran IPAS di Sekolah Dasar dan mengidentifikasi efektivitasnya dalam meningkatkan keterampilan berpikir kritis siswa. Penelitian ini mengadopsi pendekatan kualitatif dengan kerangka kerja PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) untuk memastikan transparasi dan reproduksibilitas temuan. Pengumpulan data dilakukan melalui penelusuran berbagai sumber, termasuk artikel jurnal ilmiah, literatur yang relevan, dan publikasi lainnya. Hasil penelitian ini menyatakan bahwa model ikuiri terbimbing memiliki kontribusi signifikan dalam peningkatan keterampilan berpikir kritis IPAS siswa Sekolah Dasar. Hal ini dikarenakan memungkinkan siswa untuk mengolah dan menganalisis informasi, sehingga menghasilkan sesuatu yang baru terhadap konsep yang ada. Oleh karena itu, penerapan model pembelajaran inkuiri terbimbing dalam konteks pembelajaran IPAS menjadi langkah penting dalam meningkatkan keterampilan berpikir kritis siswa sekolah dasar.